Behavioral Functioning among Mexican-Origin Children: Does Parental Legal Status Matter?(*) - Landale, Nancy S. (J Health Soc Behav, 2015)
Using data on 2,535 children included in the Los Angeles Family and Neighborhood Survey, we investigate how the legal status of immigrant parents shapes their children’s behavioral functioning. Variation in internalizing and externalizing problems among Mexican youth with undocumented mothers, documented or naturalized citizen mothers, and U.S.-born mothers is analyzed using a comparative framework that contrasts their experience with that of other ethnoracial groups. Our findings reinforce the importance of differentiating children of immigrants by parental legal status in studying health and well-being. Children of undocumented Mexican migrants have significantly higher risks of internalizing and externalizing behavior problems than their counterparts with documented or naturalized citizen mothers. Regression results are inconsistent with simple explanations that emphasize group differences in socioeconomic status, maternal mental health, or family routines.